2023
DOI: 10.2174/2210315513666221005093047
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa, a Jack of All Trades Plant in Medicine: Pharmacological Aspects in Diseases Treatment and Prevention

Abstract: Nigella sativa L. (Ranunculaceae) is one of the most widely used traditional therapeutic plants. It possesses important classes of bioactive compounds among which thymoquinone as the major bioactive component of the essential oil has attracted noteworthy attention due to its active role in treating a various range of disorders. N. sativa can induce a wide range of pharmacological functions including anti-oxidative stress responses, antidiabetic, anticancer, cell apoptosis and increase membrane permeability, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…Brain histopathology was also performed and it was the results revealed considerable glucose increases, AGEs (Advanced Glycation End Products) and aldose reductase as well reduced insulin in the diabetic neuropathy-induced category in comparison with the healthy control category. Infl ammatory markers were considerably enhanced with the diabetic neuropathy group [35]. Additionally a marked change in oxidation level was observed in the same group, a signifi cant reduction in nitrotyrosine amount was observed [26].…”
Section: Anti-diabeticmentioning
confidence: 84%
See 2 more Smart Citations
“…Brain histopathology was also performed and it was the results revealed considerable glucose increases, AGEs (Advanced Glycation End Products) and aldose reductase as well reduced insulin in the diabetic neuropathy-induced category in comparison with the healthy control category. Infl ammatory markers were considerably enhanced with the diabetic neuropathy group [35]. Additionally a marked change in oxidation level was observed in the same group, a signifi cant reduction in nitrotyrosine amount was observed [26].…”
Section: Anti-diabeticmentioning
confidence: 84%
“…A number of pharmaceutical and biological properties are attributed to cumin seeds. Akhzari, et al [35] found cumin seeds and their oil as a functional food with high dietary supplement potential, as well as traditional medicinal and biological principles of the general health benefi ts of cumin seeds (Figure 4).…”
Section: General Health Benefi Tsmentioning
confidence: 99%
See 1 more Smart Citation